The lived experience of transgender individuals living in Cape Town, South Africa - Batts, Jaymion (Department of Psychology, 2025)
This study examined the lived experiences of those who identify as transgender residing in Cape Town, South Africa. The study aimed to understand how those who identify as transgender are treated within a particular context based on their social identities (gender, sex, race and class) making use of a feminist theory—intersectionality. To explore this phenomenon, the researcher used a critical qualitative research methodology. The researcher interviewed 15 male-to-female self-identified transgender participants through a semi-structured interview schedule. The data was analysed using thematic narrative analysis. The results indicated that those who identify as transgender experience extreme forms of prejudice, ostracisation, stigmatisation, marginalisation, discrimination, and varied forms of violence (verbal, sexual and physical), because of their social identities. Furthermore, the participants reported experiencing neglect and being verbally, physically and sexually abused because of not conforming to gender norms. The participants revealed that the perpetrators inflicting these painful experiences were men. These forms of violence ultimately led to them becoming homeless and relying on external structures for support as young and vulnerable children. This had significant implications for the trajectory of those who identify as transgender, placing them at an even greater disadvantage in accessing resources. In conclusion, interventions should focus on psychoeducation and training within the following key systems: family, community, school, healthcare and the legal system. These interventions can help reduce prejudice, ostracisation, stigmatisation, marginalisation, discrimination, and violence (verbal, sexual and physical) based one's social identities. Ultimately, individuals who identify as transgender continue to face harsh life consequences, even under South Africa's new laws that prohibit discrimination based on gender, sex, race and class.